TikTok flipped classroom method in folk art courses: an investigation of teachers and learners’ perceptions - Hu, Ting; Chen, Haowei; Wang, Lin; Tan, Choon Keong (Frontiers in Education, 2025)
IntroductionThe flipped classroom method is considered to be one of the most effective strategies for implementing the necessary improvements in the field of education in the modern day. This pedagogical approach that has gained prominence in recent years, involves the reversal of standard education. This study explores the implementation of a TikTok-based flipped classroom method in a folk-art course, focusing on the perceptions and challenges faced by both students and teachers.MethodsUsing a qualitative approach, semi-structured interviews were conducted with students and teachers to gather in-depth insights. The data were analyzed through thematic analysis using NVivo 14 software, which allowed for efficient coding and the identification of emerging themes.ResultsThe findings revealed that students had overwhelmingly positive perceptions of the TikTok flipped classroom method, highlighting four key themes: learning methods, pre-class materials, learning content, and interactivity. The study also examined the factors influencing academic performance and the challenges encountered by both students and teachers in this innovative teaching approach. Through these insights, the research contributes to a better understanding of how social media platforms like TikTok can enhance engagement and learning outcomes in creative courses.